PENGARUH MOTIVASI, MINAT, DAN MANAJEMEN WAKTU TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA KELAS VII SMP - Agustin Eudya; Iwit Prihatin; Marhadi Saputro (Program Studi PGSD Universitas Flores, 2021)
The purpose of this study was to determine: (1) The effect of motivation on mathematics learning achievement; (2) The effect of interest on mathematics learning achievement; (3) The effect of study time management on mathematics learning achievement; (4) The influence of motivation, interest, and time management on the learning achievement of seventh grade students of SMP Negeri 1 Tumbang Titi. The sampling used in this study was nonprobability sampling with purposive sampling technique. The instrument for collecting data was a questionnaire. Data analysis in this study used descriptive analysis with the help of the SPSS 25 application. The results showed that: (1) There was an effect of motivation on students' mathematics learning achievement. This can be indicated by a regression coefficient of 0.712 which means that it has a positive effect on mathematics learning achievement; (2) There is an influence of interest on students' mathematics learning achievement. This can be indicated by a regression coefficient of 0.388 which means that it has a positive effect on mathematics learning achievement; (3) There is an effect of time management on students' mathematics learning achievement. This can be indicated by a regression coefficient of 0.466 which means that it has a positive effect on mathematics learning achievement; (4) There is an effect of motivation, interest and time management on students' mathematics learning achievement. This can be indicated by a regression coefficient of 0.726, which means that it has a positive effect on mathematics learning achievement.